Role of processing of N-linked oligosaccharides in control of immunoglobulin secretion from rat hybridomas - Hashim, Onn Haji; Cushley, W. (1987)
The effects of inhibition of N-linked oligosaccharide processing by glucosidase and mannosidase activities upon secretion of rat hybridoma IgM and IgG have been investigated. The inhibitor of glucosidase I, castanospermine, prevents conversion of the N-linked carbohydrate groups of IgM to a complex form as assessed by resistance to digestion by endo H. The rate of secretion of IgM or IgG from the treated cells is not diminished relative to controls. Similar data are obtained for studies employing the inhibitor of glucosidase I and II activities, 1-deoxynojirimycin. Inhibition of processing by the mannosidase inhibitors 1-deoxymannojirimycin and swainsonine leads to alteration of the qualitative structure of the oligosaccharide groups present on IgG molecules, but again has no effect upon the rate of export of IgG or IgM molecules from treated cells. In each case studied the mu or gamma heavy chains isolated from lysates or culture supernatants of cells treated with glucosidase inhibitors had a higher Mr than the equivalent chains isolated either from control cultures or cultures exposed to either mannosidase inhibitor.